POST-PARTITION CONFLICTS AND DIASPORIC LOSS IN AMITAV GHOSH AND JHUMPA LAHIRI’S NARRATIVES - Angelo Monaco (Le Simplegadi, 2016)
My article investigates Amitav Ghosh’s The Shadow Lines and Jhumpa Lahiri’s story “When Mr. Pirzada came to dine” so as to propose an analysis of narratives which best capture the antagonisms of post-Partition India. The long shadow of the 1947 Partition entailed further small-scale partitions which have marked recent Indian history. Diasporic dislocations are hence documented in such narratives which, revolving around memories of loss and tensions, unveil the transformative and ethic power of transnational literature.